CLINICAL AND THEORETICAL ASPECTS OF THE USE OF PROTAPER GOLD AND PROTAPER NEXT NEEDLE SYSTEMS IN ENDODONTIC TREATMENT - Mădălina Matea; Andreea Nicola; Adina Turcu; Adina Bunget; Marilena Bătăiosu; Cezar Diaconu; Ionela Teodora Dascălu; Ruxandra Voinea Georgescu; Mihaela Jana Țuculină (Romanian Dental Association for Education, 2021)
The main goal of endodontic treatment is to reduce the number of bacteria and their byproducts which perpetuates apical periodontitis. Effective chemo-mechanical debridement techniques on par with stringent disinfection protocols aid in possibly diminishing the bacterial load residing in the complexities of the root canal systems. The main cause of endodontic diseases is bacteria and therefore, disinfection of the root canal system is essential for successful healing and results. The anatomy of the root canal system is complex, and bacteria consider this complexity to be an environment conducive to installation and development. The treatment of the root canal consists of multiple steps in which the dentist accesses the infected canals, cleans them, then fills and seals the space to prevent reinfection. The root canal cleaning process involves modeling the canal with needles to provide enough space for the irrigation solution to disrupt the biofilm and kill bacteria along the entire length of the canal. These needles also participate in the disinfection process by removing infected dentinal debris, dead tissue, and foreign material from the root canal space. Several mechanical devices and techniques were introduced to make canal preparation easier and to further improve the effectiveness of instrumentation. The devices for root canal instrumentation may be classified as either manual or machine assisted. Machine-driven endodontic instruments help to prepare the root canals swiftly with much ease as opposed to manual instrumentation. Diverse machine-assisted techniques include automated, sonic and ultrasonic, laser systems and non-instrumental root canal preparation techniques. Therefore, these needles are essential tools for achieving the objectives of a canal treatment. Consequently, the design and metallurgy of needles have been frequently studied in the literature and many improvements have been made to increase their clinical performance